2022
DOI: 10.1159/000527095
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Correlates of Cue Reactivity in Individuals with Excessive Smartphone Use

Abstract: <b><i>Background:</i></b> Excessive smartphone use (ESU), that is, a pattern of smartphone use that shows specific features of addictive behavior, has increasingly attracted societal and scientific interest in the past years. On the neurobiological level, ESU has recently been related to structural and functional variation in reward and salience processing networks, as shown by, for example, aberrant patterns of neural activity elicited by specific smartphone cues. <b><i>Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, alpha- or delta-band activity was closely related to the degree of internet use disorder in both functional and resting states ( Balconi, Campanella, & Finocchiaro, 2017 ; Burleigh, Griffiths, Sumich, Wang, & Kuss, 2020 ; Wang & Griskova-Bulanova, 2018 ; H. Wang, Sun et al., 2020 ). Several fMRI studies also found that smartphone use disorder was associated with functional abnormalities in attention- or reward-related brain areas ( Han & Kim, 2022 ; Henemann et al., 2022 ; Pyeon et al., 2021 ). Thus, it is reasonable to speculate that topological deviations in top-down control and reward-motivated networks were associated with smartphone use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alpha- or delta-band activity was closely related to the degree of internet use disorder in both functional and resting states ( Balconi, Campanella, & Finocchiaro, 2017 ; Burleigh, Griffiths, Sumich, Wang, & Kuss, 2020 ; Wang & Griskova-Bulanova, 2018 ; H. Wang, Sun et al., 2020 ). Several fMRI studies also found that smartphone use disorder was associated with functional abnormalities in attention- or reward-related brain areas ( Han & Kim, 2022 ; Henemann et al., 2022 ; Pyeon et al., 2021 ). Thus, it is reasonable to speculate that topological deviations in top-down control and reward-motivated networks were associated with smartphone use disorder.…”
Section: Discussionmentioning
confidence: 99%